PENGARUH LEVERAGE, SALES GROWTH, DAN ARUS KAS OPERASI TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia pada Tahun 2022-2024) - Erik Pernando; Enggar Diah Puspa Arum; Ilham Wahyudi (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the effect of leverage, sales growth, and operating cash flow on financial distress in consumer cyclicals companies listed on the Indonesia Stock Exchange for the 2022–2024 period. This study uses a quantitative approach with secondary data obtained from the company's financial statements and analyzed using multiple linear regression through the classical assumption test and simultaneous (F-test) and partial (t-test) hypothesis testing. The results show that leverage, sales growth, and operating cash flow simultaneously influence financial distress. Partially, leverage has a significant positive effect, sales growth has a significant positive effect, while operating cash flow has a significant negative effect. These findings indicate that a company's funding structure and ability to generate operating cash flow are important factors in determining a company's financial condition. Therefore, companies need to manage debt and cash flow effectively to minimize the risk of financial distress. Keywords: Leverage, Sales Growth, Operating Cash Flow, and Financial Distress